An Introspect into Management Aspects of the Institutions - Case Study of the Selected FPCs in the Forest Divisions of Midnapore District, West Bengal - Sarkar, S. K.; Chattopadhyay, R. N. (Indian Forester, 1999)
This article is based on field survey to assess the performance of the Forest Protection Committees through participatory monitoring in four Forest Divisions of Midnapore District with their success and drawbacks.